1/3х+5/8х-3=1/6х-5/36, умножим каждое слагаемое на Х
1/3+5/8-3х=1/6-5/36х
-3х+(5/36)х=1/6-1/3-5/8
=
x= /
x= *
x=
8/24x+15/24x-4/24x=-5/36+3
19/24x=103/36
x=103/36*24/19
x=618/171=3 105/171
1/3х+5/8х-3=1/6х-5/36, умножим каждое слагаемое на Х
1/3+5/8-3х=1/6-5/36х
-3х+(5/36)х=1/6-1/3-5/8
x=
/ ![\frac{-103}{36}](/tpl/images/0056/6990/65392.png)
x=
* ![\frac{-36}{103}](/tpl/images/0056/6990/36095.png)
x=![\frac{19*3}{2*103}](/tpl/images/0056/6990/b0a86.png)
x=![\frac{57}{206}](/tpl/images/0056/6990/5cc8c.png)
8/24x+15/24x-4/24x=-5/36+3
19/24x=103/36
x=103/36*24/19
x=618/171=3 105/171